Management of Solid Organ Arterial Pseudoaneurysms Following Trauma - Hopkins, Peyton; Laney, Dan F., IV; Fairchild, Alexandra H.; Ustunsoz, Bahri; Ferral, Hector (Seminars in Interventional Radiology, 2025)
Management of solid organ arterial pseudoaneurysms following both blunt and penetrating trauma has become a point of increased emphasis in recent years. At present, consensus guidelines for management of post-traumatic solid organ arterial pseudoaneurysms do not exist. There is a trend in recent literature towards recommending short interval repeat imaging of solid organ trauma patients to screen for arterial pseudoaneurysm formation facilitating prompt intervention in order to mitigate the risk of delayed hemorrhage. This viewpoint, however, is not shared by all in the trauma surgery and interventional radiology communities. Nonetheless, implementation of institutional protocols based upon current literature and local expertise is a practical step in managing patients at risk for pseudoaneurysm development until consensus guidelines are developed.
Keywords: pseudoaneurysm; trauma; embolization; laceration; interventional radiology